Medical Intensive Care Unit Admission Among Patients With and Without HIV, Hepatitis C Virus, and Alcohol-Related Diagnoses in the United States: A National, Retrospective Cohort Study, 1997–2014. (1st February 2019) - Rentsch, Christopher T.; Tate, Janet P.; Steel, Tessa; Butt, Adeel A.; Gibert, Cynthia L.; Huang, Laurence; Pisani, Margaret; Soo Hoo, Guy W.; Crystal, Stephen; Rodriguez-Barradas, Maria C.; Brown, Sheldon T.; Freiberg, Matthew S.; et al.
Abstract : Background: HIV, hepatitis C virus (HCV), and alcohol-related diagnoses (ARD) independently contribute increased risk of all-cause hospitalization. We sought to determine annual medical intensive care unit (MICU) admission rates and relative risk of MICU admission between 1997 and 2014 among people with and without HIV, HCV, and ARD, using data from the largest HIV and HCV care provider in the United States. Setting: Veterans Health Administration. Methods: Annual MICU admission rates were calculated among 155, 550 patients in the Veterans Aging Cohort Study by HIV, HCV, and ARD status. Adjusted rate ratios and 95% confidence intervals (CIs) were estimated with Poisson regression. Significance of trends in age-adjusted admission rates were tested with generalized linear regression. Models were stratified by calendar period to identify shifts in MICU admission risk over time. Results: Compared to HIV−/HCV−/ARD− patients, relative risk of MICU admission decreased among HIV-mono-infected patients from 61% (95% CI: 1.56 to 1.65) in 1997–2009% to 21% (95% CI: 1.16 to 1.27) in 2010–2014, increased among HCV-mono-infected patients from 22% (95% CI: 1.16 to 1.29) in 1997–2009% to 54% (95% CI: 1.43 to 1.67) in 2010–2014, and remained consistent among patients with ARD only at 46% (95% CI: 1.42 to 1.50). MICU admission rates decreased by 48% among HCV-uninfected patients ( P -trend <0.0001) but did not change among HCV+ patients ( P -trend = 0.34). Conclusion: HCV infection and ARD remain key contributors to MICU admission risk. The impact of each of these conditions could be mitigated with combination of treatment of HIV, HCV, and interventions targeting unhealthy alcohol use. Abstract : Supplemental Digital Content is Available in the Text.